Children and Adolescents in Times of Crises in Europe - Grimm, Marc; Ertugrul, Baris; Bauer, Ullrich (Children's Well-Being: Indicators and Research, 2019)
This book presents an analysis of the impact of the social crisis on the well-being of children and adolescents in Europe. Focusing on the fields of health, employment and social status, this book highlights that the impact of crisis has to be viewed in light of the state policies in reaction to crisis. Chapters in the book offer new perspectives of a reflexive crisis research objectifying crisis and analyzing what is referred to as crisis by whom, how, for what purposes and with which implicit or explicit solutions. This book offers empirical evidence and unique analytical approaches in the field of a child- and adolescent-oriented crisis research. .